(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article deals the historical and pedagogical sources about pedagogical views in the state of Karakhanids and the significance of educational sights of thinkers in bringing up the young generation.